The neural correlates of in-group and self-face perception: is there overlap for high identifiers? - Scheepers, Daan; Derks, Belle; Nieuwenhuis, Sander; Lelieveld, Gert-Jan; Van Nunspeet, Felice; Rombouts, Serge A.; De Rover, Mischa (Frontiers in Human Neuroscience, 2013)
Social identity, the part of the self-concept derived from group membership, is a key explanatory construct for a wide variety of behaviors, ranging from organizational commitment to discrimination towards out-groups. Using functional magnetic resonance imaging, we examined the neural basis of social identity through a comparison with the neural correlates of self-face perception. Participants viewed a series of pictures, one at a time, of themselves, a familiar other, in-group members, and out-group members. We created a contrast for self-face perception by subtracting brain activation in response to the familiar other from brain activation in response to the self face, and a contrast for social identity by subtracting brain activation in response to out-group faces from brain activation in response to in-group faces. In line with previous research, for the self—familiar other contrast we found activation in several right-hemisphere regions (inferior frontal gyrus, inferior and superior parietal lobules). In addition, we found activation in closely-adjacent brain areas for the social identity contrast. Importantly, significant clusters of activation in this in-group—out-group contrast only emerged to the extent that participants reported high identification with the in-group. These results suggest that self-perception and social identity depend on partly similar neural processes.